Gendered Vulnerabilities and Violence in Forced Migration: The Rohingya from Myanmar - Salehin, Mohammad Musfequs (Palgrave Macmillan, 2024)
Intro -- Acknowledgements -- About the Book -- Contents -- About the Author -- Abbreviations -- Chapter 1: Introduction -- The Research -- Organisation of the Book -- References -- Chapter 2: Gender, Violence, and Vulnerabilities in Forced Migration: A Multi-dimensional Approach -- Introduction -- Gendered Vulnerabilities, Violence, and Migration -- Sexual and Gender-Based Violence (SGBV) -- Structural, Cultural, and Symbolic Violence -- Gender in Structural, Symbolic, and Cultural Violence -- Structural Violence, Intersectionality and the Continuum of Violence -- Conclusion -- References -- Chapter 3: The Rohingya Crisis: Background on Myanmar, the Current Conflict, and Relevant Actors -- Introduction -- Background to the Rohingya Crisis -- Actors in Conflict: The Ultranationalist Buddhists and ARSA -- The State, the Military and the Monks: A Complex Interplay -- Conclusion -- References -- Chapter 4: Gendered and Racialised Vulnerabilities and Violence Against the Rohingya in Myanmar -- Introduction -- 'Monstrous Other', Rohingya Men, and the Existential Threat to Buddhism -- Bengali Kala: From Everyday Racism to Political Rhetoric in Myanmar -- Gendered Rumours, Rohingya Women, the Military, and the Ultra-Buddhist Nationalists -- Rohingya Women, Vulnerabilities, and Sexual Violence -- Sexual Violence Against Rohingya Men and Boys -- Why Sexual Violence? -- Gendered Mobility, Discrimination, and Justice -- Intermarriage, Women, and the Monks -- Buddhist Women in the Ultranationalist Movement -- Other Forms of Violence -- Conclusion -- References -- Chapter 5: Gendered Vulnerabilities and Violence in Rohingya Refugee Camps in Bangladesh -- Introduction -- From Shaming and Ignorance to Domestic Violence -- Multiple Marriages, Child Marriages, and High Fertility -- From Personal Hygiene to Mental Trauma.